ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI TH 2010 â 2012) - Murwanti, Sri; Mulyono, Mulyono (Universitas Muhammadiyah Surakarta, 2015)
This study aims to analyze the influence of : 1 ) Return on Assets ( ROA ) to the stock price on the banking companies listed on the Stock Exchange th period 2010-2012 ; 2 ) Return On Equity ( ROE ) to the stock price on the banking companies listed on the Stock Exchange th period 2010-2012 ; 3 ) Net Profit Margin (NPM ) on stock prices in the banking companies listed on the Stock Exchange th period 2010-2012 ; 4 ) Earning per share (EPS ) to the stock price on the banking companies listed on the Stock Exchange th period 2010-2012 ; 5 ) Price Earning Ratio ( PER ) on stock prices in the banking companies listed on the Stock Exchange th period 2010-2012 ; and 6 ) ROA , ROE , NPM , EPS , PER simultaneously on stock prices in the banking companies listed on the Stock Exchange th period 2010-2012 .This research was conducted using secondary data . The population in this study are listed banking industry in Indonesia Stock Exchange ( IDX ) of 28 companies , the samples taken were 84 observations by purposive sampling technique . The method of analysis used by multiple regression analysis with first tested the classical assumptions include normality test, multicollinearity , heteroscedasticity test , and hypothesis testing used is a simultaneous significant test ( Test F ) , partial significant test ( the self- t ) .The results of this study prove that : ROA no significant effect on the stock price on the banking companies listed on the Stock Exchange th period 2010 - 2012 , ROE no significant effect on the stock price on the banking companies listed on the Stock Exchange th period 2010 - 2012 , NPM significantly influence stock price on the banking companies listed on the Stock Exchange th period 2010 - 2012 , EPS significantly influence stock prices in the banking company listed on the Stock Exchange th period 2010 - 2012 , PER no significant effect on the stock price on the banking companies listed on the Stock Exchange th period 2010 - 2012 , ROA , ROE , NPM , EPS and PER simultaneously significant effect on stock prices in the banking companies listed on the Stock Exchange th period 2010 - 2012Â